Analyze the Impact of Digital Transformation on Learning using Soft Computing - Akhtar, Naeem; Rana, Anurag; Amin, Ruhul; Nath, Hitumoni; Nath, Kalpana; Jingar, Parthvi Kirankumar; Ravindran, Selvan (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In the contemporary landscape of education, the pervasive influence of digital transformation has redefined the paradigms of learning, ushering in a new era characterized by unprecedented connectivity and technological integration. This research delves into the profound impact of digital transformation on learning methodologies, specifically through the lens of soft computing—a paradigmatic approach that harnesses the computational power of artificial intelligence to emulate human cognitive processes. Soft computing techniques, such as fuzzy logic, neural networks, and genetic algorithms, serve as instrumental tools in optimizing adaptive learning systems, personalizing educational content, and enhancing the overall efficacy of pedagogical processes. The symbiotic relationship between digital transformation and soft computing not only revolutionizes the traditional educational framework but also addresses the evolving needs of diverse learners, accommodating various learning styles and preferences. Through an analytical exploration of this interdisciplinary intersection, this paper elucidates the transformative potential of merging digital technologies and soft computing in shaping the future landscape of education. The elucidation of this intricate relationship contributes to a nuanced understanding of how technology-driven methodologies can be harnessed to foster a more inclusive and effective learning environment.